Shorter Diagnostic Delay in Polish Adult Patients With Common Variable Immunodeficiency and Symptom Onset After 1999 - Ziętkiewicz, Marcin; Więsik-Szewczyk, Ewa; Matyja-Bednarczyk, Aleksandra; Napiórkowska-Baran, Katarzyna; Zdrojewski, Zbigniew; Jahnz-Różyk, Karina (Frontiers in Immunology, 2020)
Common variable immunodeficiency (CVID) is the most clinically significant primary antibody immunodeficiency recognized in adulthood. Previously published data have shown a diagnostic delay of up to an average of 10 years for Polish adult patients with CVID. In the current study, we aimed to analyze the current diagnostic delay of adult patients with CVID in Poland. To this end, we identified patients from four immunological centers specializing in the care of adult patients with primary immunodeficiencies (PID). Demographic and clinical data of patients were collected using an internet database. We identified 103 adult patients (F:M 44.7%:55.3%) in Poland with CVID. The median age at onset of symptoms was 24 (0–66), 33 (4–70) at diagnosis, and 37 (18–73) years at the time of analysis. The median diagnostic delay for the entire study population was 6 (0–57) years. However, this delay was higher in patients with symptom onset before the year 2000 than after the year 1999 (15 (0–57) vs. 3 (0–19) years; p < 0.001). In comparing patients (median ≤ 6 years, N = 53) with short diagnostic delay (SDD) to those (median > 6 years, N = 50) with long diagnostic delay (LDD), the LDD group had a statistically significant higher incidence of infections of the lower respiratory tract before diagnosis (90.0% vs. 71.70%). During the entire observation period, cytopenias (44.00% vs. 22.64%), granulomatous lesions (28.00% vs. 11.32%), and solid tumors (14.00% vs. 1.89%) were significantly more frequent in the LDD group. In conclusion, we found a significant reduction in the median diagnostic delay in Polish CVID patients with disease onset in the two last decades.